STRATEGI KOMUNIKASI PEMASARAN LEMBAGA DESA WISATA BEJIONG DALAM MENCAPAI ANUGERAH DESA WISATA INDONESIA (The Commercium, 2023)
This research was conducted with the aim of knowing the strategies implemented by the Bejijong Tourism Village Institute in participating in the Indonesian Tourism Village Awarding, an event held by the Ministry of Tourism and Creative Economy. This research uses a type of qualitative descriptive research approach. Qualitative approach, which is to make direct observations to investigate social phenomena or humans. The main informants were the secretary of the Bejijong tourism village, the head of the Bejijong tourism village institution and representatives of members of the Bejijong tourism village institution. As for some supporting informants taken by researchers from visiting tourists. Data collection techniques used are interviews, observation, and documentation. Data analysis was carried out by collecting data, reducing data, presenting data, and concluding. The results showed that the strategy implemented by the Tourism Village Institute was a marketing mix of 7p product, price, place, promotion, people, physical evidence, and process. There are also findings that support and inhibit the marketing strategy carried out by the Tourism Village Institute. Supporting factors include management which includes services, historic locations and community support, clean, tidy and unique locations. The inhibiting factors are natural resources and language.